2012
DOI: 10.1007/s00417-012-2135-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between reading speed, cycloplegic refractive error, and oculomotor function in reading disabled children versus controls

Abstract: This research indicates there are significant associations between reading speed, refractive error, and in particular vergence facility. It appears sensible that students being considered for reading specific IEP status should have a full eye examination (including cycloplegia), in addition to a comprehensive binocular vision evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 18 publications
6
38
0
3
Order By: Relevance
“…Our findings are comparable with previous reports suggesting that children with visual function anomalies could be at disadvantage in reading, writing and academic performance [5,12,13,25,[29][30][31][32][33][34]. Some studies support the possibility that children with unstable binocular control commit more phonological spelling errors, even when age, IQ and phonemic awareness were taken into account [29].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are comparable with previous reports suggesting that children with visual function anomalies could be at disadvantage in reading, writing and academic performance [5,12,13,25,[29][30][31][32][33][34]. Some studies support the possibility that children with unstable binocular control commit more phonological spelling errors, even when age, IQ and phonemic awareness were taken into account [29].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study has shown a significant association between reading speed, refractive error, and in particular vergence facility in subjects with reading difficulties. 23 Other studies have also shown that orthoptic training is effective in improving vergence ability (as was also found for the positive fusional reserves at near in this study) and fixation disparity. [16][17][18][19] Brautaset and Jennnings found improved positive vergence at near after orthoptic training on subjects with convergence insufficiency.…”
Section: Discussionsupporting
confidence: 86%
“…In both studies, the group with reading difficulties had significantly reduced performance on several measures of binocular vision, but astigmatic refractive error did not differ between groups. 25,26 In contrast, two studies using school-based samples found significant relations between astigmatism and academic performance and readiness in children. 27,28 In a study of Navajo (Diné) Native American school children, who have a high prevalence of astigmatism, Garber reported that uncorrected astigmatic 5 th and 6 th grade students (≥2.00D) had poorer teacher-assigned reading scores than non-astigmatic students, but found no significant effect of astigmatism on reading scores from standardized tests in 2 nd grade students.…”
Section: Discussionmentioning
confidence: 95%